Tinjauan Hukum Kriminalisasi Berita Hoax: Menjaga Persatuan vs. Kebebasan Berpendapat - Cindy Bella Devina; Dissa Chandra Iswari; Go Christian Bryan Goni; Devi Kimberly Lirungan (Universitas Muhammadiyah Purwokerto, 2021)
The existence of hoaxes in Indonesia has been around for a long time. However, the term hoax was widespread and became part of daily conversations in the media and the public during the 2014 and 2019 Presidential Election. The rapid development of social media use and the ease of information exchange accelerated the spread of hoax. Even in the COVID-19 pandemic, hoax news about the corona virus and matters related to it are widespread in the community. This hoax news, both during the Election and the Covid-19 Outbreak, caused much unrest in the community. Some of the hoax news spreaders were jailed for violations of the ITE Law. Various legal practitioners and academics have also suggested that hoax news creators and spreaders be criminalized. This article reviews normatively whether the criminalization of hoax news is feasible for reasons of maintaining stability or needs to be eliminated to maintain freedom of opinion. The author reviews the normative aspects of criminalizing the creation and dissemination of hoax news by using Habermas' theory of deliberative democracy. Through this theory, the writer finds that hoax news makes aspects of democracy such as dialogue that is full of awareness and accurate information unattainable. This is also in line with what the Indonesian constitution wants. However, it is necessary to ensure that the criminalization of hoaxes is not used as an instrument of abuse of power considering that the circulation of hoaxes is a symptom of a problem rather than the root of the problem itself.Keywords: Fake News, Criminalization, Stability, Freedom of Speech, Deliberative Democracy, Legal Revuew